Finite element method simulations of heat flow in fixed bed solar water splitting redox reactors - SHVETS, IGOR; LUBBEN, OLAF; KRASNIKOV, SERGEY; MURPHY, BARRY; BULFIN, BRENDAN (My University, 2012)
An improved design for radiation absorption and heat flow into materials with low thermal conductivity is demonstrated. The design was developed for application in fixed bed two step solar water splitting redox reactors. The fixed bed was assumed to be made from porous ceramic. The low thermal conductivity of the porous ceramic redox material is compensated for by changing the profile of the fixed bed. The profiling used was wedges cut into the material which allows concentrated solar radiation to be incident on a larger area of redox material than for a flat monolith design. The design is demonstrated to efficiently transfer heat to the bulk and greatly reduce re-radiation. For a wedge 9 cm in depth and 1.6 cm wide at the opening, heated with 500 kWm 2 incident radiation for 300 s, approximately double the amount of radiation is absorbed. The effects of thermal conductivity, emissivity and scaling on the efficiency of the design were investigated. The radiation absorption performance improved when scaled up. The improvement of the design over a flat plain bed is greater for lower emissivity. The improvement provided by the wedge design was found to decrease for increasing thermal conductivity, and eventually for high conductivity values it reduced performance. Using this method a larger amount of material with low thermal conductivity can be heated with the same power input and reduced radiation losses. The heat flow simulations were then coupled to an Arrhenius rate equation to investigate the possible improvement to the reaction efficiency and yield offered by the wedge design. Over a time of 300 s the efficiency and yield were seen to be approximately a factor of 4 times higher in the wedge case. Finally a concentrated solar cavity reactor based on the design is proposed.
PUBLISHED
Available on-line 05 May 2012
Keywords: hydrogen production; redox reactors; water splitting; efficiency; heat flow; Nanoscience & Materials